Trans Tracheal Approach to the Oesophagus: Case Report - Angelica Lynch; Chris Perry; Bernard Mark Smithers; Raefe Gundelach; Daniel Rowe (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2016)
Hypopharyngeal squamous cell carcinoma (SCC) is a rare form of malignancy and treatment approach is most commonly with chemo-radiotherapy or total pharyngolaryngoesophagectomy. We report a case of hypopharyngeal SCC managed with local resection and larynx preservation in a 77-year-old-woman. Total pharyngolaryngoesophagectomy renders patients with an alteration in both voice and ability to swallow hence carrying signifi cant post-operative morbidity. We review the literature for similar larynx-preserving operations and illustrate a novel approach to the management of this rare malignancy.